THE SYNERGY OF HUMAN AND AI CREATIVITY: AN EXPERIMENT IN CO-CREATING EFFECTIVE MARKETING CONTENT - Ma’rifah; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
This study explores the synergy between human and artificial intelligence (AI) creativity in the co-creation of effective marketing content. As generative AI tools become increasingly integrated into marketing practices, understanding how human and AI capabilities interact has become essential. Using an experimental approach, this research compares human-created, AI-generated, and co-created content across key dimensions, including creativity, authenticity, engagement, and overall effectiveness. The findings reveal that while human-created content excels in emotional depth and authenticity, and AI-generated content demonstrates strengths in efficiency and scalability, co-created content consistently achieves the most balanced and effective outcomes. Perceived creativity and authenticity emerge as critical mediating factors that influence consumer responses, shaping trust, engagement, and persuasive impact. The study also highlights the role of moderating factors such as consumer familiarity with AI and task complexity in determining the effectiveness of different content creation modes. A conceptual framework is proposed to explain the relationships between content creation mode, perceptual mediators, and marketing outcomes. This research contributes to the literature on hybrid creativity and provides practical insights for marketers seeking to optimize content strategies through human–AI collaboration.